The Architectural Characteristics Linkage Between Batanghari Hulu's Traditional House With Tanah Datar's Rumah Gadang - Muhammar Khamdevi (Universitas Bandar Lampung (UBL), 2022)
Jambi and West Sumatra has shared history from the days of the Old Malay Kingdom, Sriwijaya, Dharmasraya, Malayupura. The traditional house of Rumah Gedang in the Upperstream Batanghari River region seem to have similarities with the Rumah Gadang in the Rantau and Darek Tanah Datar areas. No researcher has tried to discuss the relationship among them. Therefore, this study tries to explore the Architectural Characteristics of the two buildings. This study uses a qualitative method by comparing the architectural characteristics of the two buildings from the data obtained in the field. The results of the study indicate a link between the two buildings.